Which was the original sin? Translations and interpretations from Gn 3, 1-24 (Circe de clásicos y modernos, 2018)
This paper analyzes the Greek version of Gn 3, 1-24 in connection with other interpretations of the Biblical verses, such as Philo of Alexandria’s works, the Epistle to the Romans and Ambrose’s On Paradise. In the Genesis man is presented as a being who is naturally bent to bad inclinations that move him to err and be ashamed in front of God, asimilar view also Philo shares. By taking concepts from Pauline and apocalyptic literature, Ambrosius shows an imperfect man who is weak and easily deceived by the devil. In all cases, salvation is possible: in the Genesis and Legum Allegoriae, through the kindness of God who trusts in man’s natural goodness; in Christian texts, though man is born sinful, Christ allows for his redemption and sanctification.
Keywords: Genesis; interpretation; paradise; sin; Christianity